Total phosphorus content in meat products on the market of the Republic of Serbia and regulatory compliance - Petričević Maja; Stanišić Nikola; Keškić Tanja; Petričević Veselin; Nikšić Dragan; Pisinov Boris; Stamenić Tamara (Biotechnology in Animal Husbandry)
This study focused on monitoring the phosphate levels in meat products on the Serbian market over a two-year period and evaluating the producers' compliance with regulations on additive usage. During the mentioned period, 74 different meat products (222 samples in total) were analyzed, including finely and coarsely minced cooked sausages. The analysis was conducted using the standard method (SRPS ISO 13730:1999) at the Institute of Animal Husbandry, Belgrade - Zemun laboratory. Content of total phosphorus expressed as P2O5 varied between 2.01 g/kg and 6.98 g/kg for finely minced sausages, while for coarsely minced sausages, it ranged from 4.13 g/kg to 7.97 g/kg. The results show that producers incorporate phosphates in line with the specified limits.